2020
DOI: 10.1267/ahc.20-00014
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Annexin A10 Expression Is Associated with Poor Prognosis in Early Gastric Cancer

Abstract: Gastric cancer (GC) is the third most common cause of cancer-related mortality. The diagnosis and treatment of early GC is a crucial strategy for prognostic improvement of GC. Annexin A10 (ANXA10), a calcium-/phospholipid-binding protein, is a member of the annexin family. The significance of ANXA10 expression in early GC remains unclear. This is the first report to investigate ANXA10 expression in early GC. We performed immunohistochemistry to evaluate ANXA10 expression in early GC, and the correlation betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…However, the most interesting observation was the significance of ANXA10 expression in SBA. Previous reports have shown that ANXA10 is an independent prognostic factor in several carcinomas: hepatocellular carcinoma (12), cholangiocarcinoma (24), ovarian cancer (25), thyroid cancer (26), and early gastric cancers (15). These results suggest that ANXA10 immunostaining is a clinically significant modality to predict survival of SBA patients.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…However, the most interesting observation was the significance of ANXA10 expression in SBA. Previous reports have shown that ANXA10 is an independent prognostic factor in several carcinomas: hepatocellular carcinoma (12), cholangiocarcinoma (24), ovarian cancer (25), thyroid cancer (26), and early gastric cancers (15). These results suggest that ANXA10 immunostaining is a clinically significant modality to predict survival of SBA patients.…”
Section: Discussionmentioning
confidence: 60%
“…In SBA tissue, ANXA10 expression was detected in the nuclei and cytoplasm of tumour cells (Figure 2E and F). We defined immunostaining as positive if 10% of the SBA cancer cell nuclei showed visible signals, according to previous studies (14,15). A total of 17 (56.7%) SBA samples showed ANXA10 expression.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The expression of short isoform mRNA of annexin A10, previously mistaken as annexin A10, was associated with favorable prognosis in hepatocellular carcinoma [ 11 ]. Expression of annexin A10 was associated with good prognosis of diffuse-type gastric carcinoma [ 12 , 13 ], but poor prognosis in intestinal-type gastric carcinoma, papillary thyroid cancer, small bowel adenocarcinoma, and serous epithelial ovarian cancer [ 13 16 ]. A recent study reported that annexin A10 expression was associated with poor prognosis for the perihilar and distal cholangiocarcinoma but not for the intrahepatic cholangiocarcinoma.…”
Section: Introductionmentioning
confidence: 99%